2019
DOI: 10.1186/s12879-019-4086-0
|View full text |Cite
|
Sign up to set email alerts
|

Serologic testing of randomly selected children after hepatitis B vaccination: a cross-sectional population-based study in Lao People’s Democratic Republic

Abstract: Background Population immunity against hepatitis B virus (HBV) in Lao People’s Demographic Republic (PDR) has not been examined since the national HBV vaccination program was started in 2002. Vaccine has been observed to be frozen at times during cold-chain transport in vaccination programs in Lao PDR and other developing countries, which will inactivate the vaccine. Therefore, this study used post-vaccination serologic testing to evaluate the effects of HBV immunization in Lao PDR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
(41 reference statements)
2
21
1
Order By: Relevance
“…A study from South Korea and Japan was found anti-HBs titres in 50% children were seronegative by 7 years and zero by 13 years. They recommend one booster dose if post vaccination screening is suggestive at the age of 12 -14 years [18] [24]. A beautiful systematic review and meta-analysis from 12 countries was done by Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…A study from South Korea and Japan was found anti-HBs titres in 50% children were seronegative by 7 years and zero by 13 years. They recommend one booster dose if post vaccination screening is suggestive at the age of 12 -14 years [18] [24]. A beautiful systematic review and meta-analysis from 12 countries was done by Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of HBV surveillance and limited access to testing undermine efforts to assess HBV treatment and disease burden in the whole country. In recent years, studies investigated the prevalence of chronic infection among mothers and their children as well as protection levels due to vaccination [12,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The country suffered several outbreaks of vaccine-preventable diseases, such as diphtheria and measles, despite improved vaccination coverage (14-17). Some studies reported that seroprevalence or seroprotection rates of these diseases were low (14-16) (19).…”
mentioning
confidence: 99%
“…Proposed explanations included a low immunization coverage, reduced response to vaccines in individuals due to immune deficiencies, suboptimal nutritional status, and parasite infestation (14) (16) (18) (19). In addition, some authors also suggested that challenges in cold chain management might have affected vaccine effectiveness (14-16) (18) (19).…”
mentioning
confidence: 99%